COVID-19 Infection and Gut Microbial Dysbiosis Among Filipinos with Type 2 Diabetes Mellitus - Velasco, Adrian Jonathan; Dalmacio, Leslie Michelle (Journal of the ASEAN Federation of Endocrine Societies, 2026)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:ff0898ea-2523-42a1-aa06-e95bec6fcf26-6" data-testid="conversation-turn-14" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="83d66557-7d66-43ca-88db-40f2a9b17d69" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> Background. Both type 2 diabetes mellitus (T2DM) and COVID-19 are associated with gut microbial alterations. It remains unclear whether COVID-19 causes further gut dysbiosis among individuals with T2DM. Objective. This study aimed to characterize the gut microbiome of Filipinos with T2DM who had COVID-19. Methodology. 101 Filipinos, aged 30–59, residing in the Greater Manila Area, were recruited into one of four groups: non-COVID/non-T2DM (A), COVID-recovered/non-T2DM (B), non-COVID/T2DM (C), and COVID-recovered/T2DM (D). Gut microbial composition was characterized through 16S rRNA gene profiling of stool samples using Illumina MiSeq-next-generation Sequencing. These sequences were subjected to mothur and PICRUSt2 for taxonomic and functional analyses. Results. Gut microbial analysis revealed potential disease biomarkers, as Roseburia is more abundant among participants with COVID-19 history, while Parabacteroides is more abundant among participants with T2DM. Principal coordinate analysis (PCOA) revealed that participants with T2DM clustered together, while participants without T2DM displayed significantly different clustering. Conclusion. These findings suggest that COVID-19 does not cause further gut dysbiosis among individuals with T2DM and that T2DM exerts a stronger influence on the gut microbiome compared to COVID-19. These findings are useful for clinicians to better understand the COVID-19 risk to T2DM.